Les analyses physico-chimiques et microbiologiques du lait cru l’unité GIPLAIT-MOSTAGANEM- - MELLOUKI, ABDELGHANI (My University, 2021)
Milk has always been an essential food item in our diet, in a general context where consumer demand is always oriented towards quality products. The purpose of the study carried out is to assess the physicochemical and microbiological quality of raw milk and packaged pasteurized milk In order to provide consumers with good quality milk, the raw material used and the finished product manufactured, must be subject to very strict control. The physicochemical results obtained generally comply with company standards. From a bacteriological point of view this milk has an acceptable quality .Therefore, the quality of raw cow's milk depends on the feeding of dairy cows, the milking conditions, maintenance and the breeding structure.
Keywords: raw milk; physico-chemical quality; microbiological quality.